An Open-Label Single-Arm, Monocentric Study Assessing the Efficacy and Safety of Natural Pterostilbene (Pterocarpus marsupium) for Skin Brightening and Antiaging Effects - Majeed M; Majeed S; Jain R; Mundkur L; Rajalakshmi HR; Lad PS; Neupane P (Dove Medical Press, 2020)
Muhammed Majeed, 1–4 Shaheen Majeed, 1–4 Renuka Jain, 1, 4 Lakshmi Mundkur, 1 HR Rajalakshmi, 4 Prachi Subhash Lad, 4 Prakriti Neupane 4 1Sami Labs Limited, Bangalore, Karnataka, India; 2Sabinsa Corporation, East Windsor, NJ, USA; 3Sabinsa Corporation, Payson, UT, USA; 4ClinWorld Private Limited, Bangalore, Karnataka, IndiaCorrespondence: Renuka JainSami Labs Limited, 19/1 and 19/2, First Main, Second Phase, Peenya Industrial Area, Bangalore 560 058, Karnataka, IndiaEmail renuka@samilabs.comBackground: Both intrinsic and environmental factors play a role in premature ageing of the skin. Natural extracts have been extensively used to reduce the signs of ageing in recent years. Pterostilbene is a natural analog of resveratrol with therapeutic properties against numerous diseases mainly due to its ability to reduce reactive oxygen species.Methods: We studied the anti-aging and skin brightening effect of a 0.4% formulation of natural pterostilbene in healthy volunteers (N=38) in an open-label, single-arm, monocentric study for 8 weeks. The melanogenesis inhibitory, anti-tyrosinase and anti-collagenase and anti-elastase properties of pterostilbene were evaluated in vitro.Results: Natural pterostilbene showed significant inhibition of melanogenesis in vitro. Pterostilbene cream (0.4%) was highly effective in reducing markers of aging and induces even skin tone. The product was effective in reducing wrinkles and fine lines, improved skin hydration elasticity and showed no adverse effects.Conclusion: Our results suggest that natural pterostilbene is a safe and effective ingredient for use in cosmetic preparation to reduce the markers of skin ageing and brighten the skin tone.Trial Registration: Clinical Trial Registration India Identifier CTRI/2019/01/017160 [Registered on 18/01/2019].Keywords: natural pterostilbene, Pterocarpus marsupium, skin brightening, antiaging